The Effect of Caring and Spirituality Mental Health Training (Keswacarri) on Commitment and Role of Mental Health Cadres in The District Of Widang Tuban, Indonesia - Yusuf, Ah; Hanim, Nur Faizah; Agustina, Nina; Sari , Esti Yunita; DA , Sestu Retno (International Journal of Psychosocial Rehabilitation, 2020)
The mental health cadres have several roles to play, in this case focusing on mental health issues, either in people with mental disorders or families. Negative stigma in public about mental disorder, occupying its own space in providing services to the community so it is also necessary an intake to cultivate a good commitment to the health cadres, in this case, is Keswacarri training. Experiment research with quasi-experiment. The Population of the research is 34 cadres. Collecting samples using questioner and checklist and analysis using Mann Whitney test and Wilcoxon signed rank test with a significant level of α=0,05. Result and Analysis: there was an increasing percentage of pretest and post-test. The result of Wilcoxon Signed Rank Tests for commitment and role obtained value p=0,000, and the mean there is an effect of caring and spirituality mental health training (Keswacarri) on commitment and role of mental health cadres. Keswacarri training can affect the commitment and role of mental health cadres, so hopefully Keswacarri training can be used as a reference to conduct training elsewhere.